2020
DOI: 10.1123/jpah.2019-0205
|View full text |Cite
|
Sign up to set email alerts
|

Toward Harmonized Treadmill-Based Validation of Step-Counting Wearable Technologies: A Scoping Review

Abstract: Background: The authors conducted a scoping review as a first step toward establishing harmonized (ie, consistent and compatible), empirically based best practices for validating step-counting wearable technologies. Purpose: To catalog studies validating step-counting wearable technologies during treadmill ambulation. Methods: The authors searched PubMed and SPORTDiscus in August 2019 to identify treadmill-based validation studies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 81 publications
(116 reference statements)
1
26
0
Order By: Relevance
“…Notably, prior research on wearable technologies has reported that wrist-worn devices can significantly over-or underestimate energy expenditure [37] and called for increased accuracy in wrist-worn devices due to low validity findings [38]. Specifically, a review by Moore et al [39] reported that median aggregated values of step count mean absolute percentage error (MAPE) error representing the comparison between direct observation and wearable technologies were higher for wrist-worn devices (MAPE = 7 to 11%) than for waist-worn (MAPE =1 to 4%), or thigh-worn (MAPE ≤1%).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, prior research on wearable technologies has reported that wrist-worn devices can significantly over-or underestimate energy expenditure [37] and called for increased accuracy in wrist-worn devices due to low validity findings [38]. Specifically, a review by Moore et al [39] reported that median aggregated values of step count mean absolute percentage error (MAPE) error representing the comparison between direct observation and wearable technologies were higher for wrist-worn devices (MAPE = 7 to 11%) than for waist-worn (MAPE =1 to 4%), or thigh-worn (MAPE ≤1%).…”
Section: Discussionmentioning
confidence: 99%
“…Also, children (5-9 years of age) walked with significantly different step time, cycle time, cycle frequency and cadence than their adult peers (19-32 years of age) in walking and running tests [16]. It is therefore critical to consider such threats to validity when comparing performance of step counting wearable technologies using standardized methods and validation metrics among a cohort of children [17].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of step counting wearable technologies should then be compared to this criterion standard [18]. Standardized and harmonized validation indices, specifically accuracy, bias, and precision are also necessary to facilitate comparability of different types of wearable technologies [17,19,20]. The CTA [18], Welk et al [20], Walther et al [19], and a previous scoping review from our research group [17], recommended that accuracy (defined as the overall distance between estimated or observed values and the true value [19]) be determined using mean absolute percentage error (MAPE,), calculated as follows:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These standards provide guidance for researchers to evaluate research-grade devices as well as commercial devices used by the lay public. Since the CTA released their standards for protocol and validation, researchers have begun to acknowledge them in their designs for step count [6][7][8][9], and HR [10][11][12]. However, only limited studies have actually implemented these standards [6].…”
Section: Introductionmentioning
confidence: 99%